(untitled) (Research, Society and Development, 2018)
The district of Ipoema, Itabira (MG), corresponds to an ecotourism destination due to its natural attractions, represented by several waterfalls and the Mata do Limoeiro State Park. Thus, this work aimed to evaluate the water quality, through indexes, of the Macuco Stream tributaries, a water course that makes up Paredão and Derrubado waterfalls, located in the Mata do Limoeiro State Park. The sample used in this research corresponded to seven points sampled along the Macuco Stream and its tributaries between May and August 2017. Regarding the results obtained, the Water Quality Index was in the "good" and " "Medium", while the Trophic State Index pointed to the non-eutrophication of the water bodies analyzed. However, in relation to the Balneability Index, the sampling points located upstream of Mata do Limoeiro State Park and Alta Waterfall showed a high concentration of Escherichia coli, not within the limits recommended by the Resolution of the National Environmental Council nº 274/2000. The results obtained may be associated to the use and occupation of the soil as pasture area in the region, given the possibility of access of animals to these sites. Thus, it is recommended that environmental education be developed with the local population to raise awareness about the importance of preserving natural resources in order to maintain the balance of the aquatic ecosystem.